Affective health and masculinities in South Africa - Reihling, Hans, author.
1 online resource.
Keywords: "Affective Health and Masculinities in South Africa explores how different masculinities modulate substance use, interpersonal violence, suicidality, and AIDS as well as recovery cross-culturally. With a focus on three male protagonists living in very distinct urban areas of Cape Town, this comparative ethnography shows that men's struggles to become invulnerable increase vulnerability. Through an analysis of masculinities as social assemblages, the study shows how affective health problems are tied to modern individualism rather than African 'tradition' that has become a cliché in Eurocentric gender studies. Affective health is conceptualized as a balancing act between autonomy and connectivity that after colonialism and apartheid has become compromised through the imperative of self-reliance. This book provides a rare perspective on young men's vulnerability in everyday life that may affect the reader and spark discussion about how masculinities in relationships shape physical and psychological health. Moreover, it shows how men change in the face of distress in ways that may look different than global health and gender transformative approaches envision. Thick descriptions of actual events over the life course make the study accessible to both graduate and undergraduate students in the social sciences. Contributing to current debates on mental health and masculinity, the volume will be of interest to scholars from a number of disciplines including anthropology, gender studies, African studies, psychology and global health"--